1974
DOI: 10.1037/h0036955
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials during stimulus selection in eyelid conditioning in the rabbit (Oryctolagus cunigulus).

Abstract: Rabbit eyeblinks were conditioned to either the visual or the nonvisual element of a compound conditioned stimulus. Evoked potentials (EPs) were simultaneously recorded from the visual cortex. Changes in the late negative component of the EP were related to nonspecific arousal effects. The initial surface positive component, however, was significantly enhanced during visual stimulus control. This enhancement was observed whether the visual stimulus was presented alone or in compound and with either photic or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
1

Year Published

1974
1974
1998
1998

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
3
5
1
Order By: Relevance
“…Moreover, the observation of Bear It should also be emphasized that the present authors recognize the possibility of specific as well as nonspecific influences on neurons at lower levels in the hierarchy. Work from our laboratory has shown that during attention to visual stimuli there is a specific enhancement of visual cortical evoked potentials, which cannot be attributed to changes in arousal (Kinkaide & Walley, 1974). However, in contrast to Feeney et al, we do not feel that such a mechanism is sufficient to account for selective attention.…”
contrasting
confidence: 87%
“…Moreover, the observation of Bear It should also be emphasized that the present authors recognize the possibility of specific as well as nonspecific influences on neurons at lower levels in the hierarchy. Work from our laboratory has shown that during attention to visual stimuli there is a specific enhancement of visual cortical evoked potentials, which cannot be attributed to changes in arousal (Kinkaide & Walley, 1974). However, in contrast to Feeney et al, we do not feel that such a mechanism is sufficient to account for selective attention.…”
contrasting
confidence: 87%
“…As described earlier (Kinkaide & Walley, 1974), the cortical response evoked by optic chiasma stimulation consists of two or three surface positive waves (PI, P2, and P3) followed by a large slow surface negative wave (N3) reaching a peak between 100 and 200 Figure 3 shows the mean percentage changes in amplitude for PI (dark bars) and N3 (double cross-hatched bars) relative to the pretest baseline for the seven test sessions in which V was presented alone. For PI and the geniculate AEPs, the V-alone condition was used as a baseline.…”
Section: Cortical Evoked Potentialsmentioning
confidence: 69%
“…The apparatus and the surgical and recording procedures have been described elsewhere (Kinkaide, 1974;Kinkaide & Walley, 1974) and are only summarized here. Departures from these earlier studies are described in detail.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations